Benefits of travel time savings for freight transportation : beyond the costs - Jérôme Massiani (European Regional Science Association (ERSA), 2003)
The purpose of this presentation is to investigate whether current practices in Cost Benefit Analysis do not underestimate the actual benefits accruing to the economy when transport investment reduces transport time. In a first section we define the different time related attributes of transport. We differentiate the various time dimensions of freight transportation services (time, reliability, frequency, responsiveness, etc). We decide to focus our analysis on Travel Time savings. We also investigate the meaning of the expression value of time in the specific context of freight transportation. We also recognise the variability of time perception among freight operators and between circumstances. In a second section we investigate the current practices in various European countries. We find that the overwhelming majority of countries estimate the benefits of improved network through the reduction in transport costs. However there is a strong case that the total benefits may exceed this mere cost reduction. In a third section, we show that shippers exhibit a significant willingness to pay for faster deliveries. This may have different causes like potential reorganisation of the production and distribution process, trading time consuming production technique against transport time, or increasing the time dimension of goods and services. This question should be carefully distinguished from the recurrent question about indirect effects. If direct effects are those that are captured by the supplier and consumer surplus of the market under study, then the potential extra benefit that are scrutinised in the study are part of the direct and not indirect effects. We also demonstrate that a benefit analysis based on traditional definitions of surplus should take into account these additional effects. We try to identify methods to measure these extra benefits. We review results obtained by previous attempts to measure this willingness to pay, based on RP data and SP exercises. We present the benefits and drawbacks of different measurement methods. Eventually, we show the impact of taking into account these extra benefits on projects' evaluation. and test the sensibility of Cost Benefit Ratio on a set of typical road investment projects in the U.K.
Keywords: 330